The Actuality of the Permanent Neutrality of a State in Contemporary International Law - R. Czachor (Московский журнал международного права, 2021)
INTRODUCTION. The permanent neutrality of a state is an institution of public international law that embraces both treaty and customary norms. Despite its legal character, the term ‘neutrality’ is also employed in a political context as a kind of foreign policy of a country. Recent developments in international relations, incremental cooperation within integrational structures raise a question about the current state and future perspectives of the permanent neutrality of a state. The goal of the following paper is to discuss contemporary legal status, the content and the possible future role of the permanent neutrality of a state under international law. The author critically discusses different opinions already presented in the doctrine, especially in regard to the case of Turkmenistan.MATERIALS AND METHODS. The paper analyzes international legal acts, the customary law of permanent neutrality, including the acquisition of this status, duties and rights as well as the doctrine – works of prominent legal scholars. The research was conducted upon general scientific methods, including comparative and formal-legal methods.RESEARCH RESULTS. The paper tackles the issue of the legal character of the permanent neutrality of a state and its distinctive features from the policy of neutrality. Subsequently, it discusses the problem of the evolution of permanent neutrality and provides arguments in favour of the thesis of its ‘obsolete’ nature. The analysis of the rights and obligations that stem from the permanent neutrality and their compatibility with the UN Charter’s norms brought the author to the conclusion regarding the necessity of a revival of the permanent neutrality. According to the case of Turkmenistan, the paper discusses the possible evolution of the acquisition of the status of the permanent neutral state. This could be possible through recognition by the international organization and, subsequently, hardening the soft law (the resolutions of the UN General Assembly). Finally, it presents possible salient tasks of the permanent neutral countries regarding the international society.DISCUSSION AND CONCLUSIONS. The prohibition of the use of force in international relations and the adoption of the UN Charter have raised a question regarding the prospects of permanent neutrality as an institution of public international law. The fundamental aim of this institution is to protect the sovereignty of the permanent neutral state, which currently is regulated by iuris cogentis norms. Thus, some scholars have argued that permanent neutrality is ‘obsolete’ and should disappear from international relations and particularly frominternational law. Despite that, only after the end of the ‘cold war’ growing interest to the permanent neutrality was expressed by such nations, like Belarus, Moldova, and Serbia. To conclude, permanent neutrality is still present in public international law, there are no pieces of evidence of neglecting this status by the states. Its specificity is determined by treaty laws and customary laws related to the Swiss case. The permanent neutrality possesses a constitutive character that should be confirmed by other countries. The case of Turkmenistan may open a new possibility of obtaining this status through recognition by the international organization. In general, permanent neutrality keeps important for the stability and predictability of international relations.